Perancangan Autolamp pada Mesin Cutting untuk Meminimasi Produk Cacat Menggunakan Metode QFD di CV. XYZ - Rahmi Nur Afifah; Marina Yustiana Lubis; Yunita Nugrahaini Safrudin (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Current technological developments benefit the Indonesian garment industry. Garment business must continue to innovate and improve the quality of their products in order to compete in an increasingly competitive market. CV. XYZ is a garment company in Bandung with superior products PDL shirts. The company is facing conflicts over fabric cutting process defects that have not been controlled. It is not yet known exactly the root cause of the cutting process resulting in high product defects. The purpose of this study is to determine the causes of high defects in the cutting process and design improvement strategies in the cutting process that suit user needs. The method used is FMEA which aims to determine the highest causes of defects in the cutting process so that strategies are obtained to minimize product defects, and the QFD method is used to design improvement strategies in the cutting process.. The results of the FMEA analysis found that the main cause of defects in the cutting process was eye fatigue in the operator caused by insufficient lighting in the cutting area. Using the QFD method produces an autolamp design that is integrated into the cutting machine with the function of providing lighting to the cutting area to make it easier for operators to see the fabric cutting pattern area. By using the QFD method in designing autolamp on cutting machines, it can produce product designs that meet the needs of cutting operators and have optimal features.